Monitoring of Heavy Metal Pollution in Water and Sediments at the Mid-Black Sea Region by Using Passive Sampling Method Diffusive Gradients in Thin Films - Arife Şimşek; Şule Sancak; Gülfem Bakan (Turkish Journal of Agriculture: Food Science and Technology)
Determining the potential bioavailability of heavy metals, evaluating according to adapted regulations is essential to efficiently conserve our coastal and estuarine waters. In this study, it is aimed to determine the industrial pollution and various other pollution sources that the Black Sea Basin is exposed to by using DGT (Diffusive Gradients in Thin Films) method and grab (manuel) sampling method in water and sediment and to evaluate the existing pollution according to quality standards. In Samsun, seasonal samples were collected from five different sampling stations, namely Akkiraz Stream, Hıdırellez Stream, Organized Industrial Zone (OIZ) Channel, Şabanoğlu Stream and Selyeri Stream, which are selected from Tekkeköy region where industry is intensively active. In order to determine the heavy metal content in both water and sediment samples, the DGT method was chosen for passive sampling and the grab sampling method was used for active sampling, and the efficiency of the methods was evaluated. According to the results of the study, the heavy metal concentration in grab sampling for water samples in descending order Al> Fe> Zn> Pb> Ni> Cu; In the samples taken with DGT, they are listed as Al> Fe> Zn> Cu> Ni> Pb. There were significant relationships between the total metal concentrations of sediment (Csed) and water (Csu) in grab sampling and metal concentrations sediment (Csed-DGT) and water (Csu-DGT) measured by DGT. It was found that the sensitivity and performance of sampling with DGT was 2-10 times higher compared to grab sampling. The high resolution in situ DGT technique for the assessment and management of the potential release risk of heavy metals at the water-sediment interface is a complementary method that contributes to the standard grab sampling method.